Should drinking during pregnancy be criminalised to prevent fetal alcohol spectrum disorder - Jillian Gardner (South African Journal of Bioethics and Law, 2016)
The harmful effects of alcohol use during pregnancy have been well documented. Fetal alcohol spectrum disorder (FASD) is the collective term encompassing the various clinical diagnoses that can occur in a child who was exposed to alcohol prenatally. The affected child suffers a range of lifelong primary and secondary disabilities. There is no cure for FASD, but it is preventable if women do not drink during pregnancy. Should women be banned from, and/or punished for drinking during pregnancy for the sake of preventing fetal harm? This article considers the appropriateness of criminalising drinking during pregnancy as a means of preventing fetal harm and consequently FASD in children, and concludes that criminal approaches are unjustified, potentially discriminatory and likely to be ineffective.